Istoriografsko–metafikcionalni aspekti pripovedanja Barnsove Istorije sveta (Philologia, 2021)
The paper examines the modes of establishing the narrative identity, whether that be via the historiographic and metafictional aspects of narration, or by means of a paradoxical dialectical process of the subject self–establishment through the narrative process as such. The paper also re–examines the issues raised by Linda Hutcheon’s theoretical tenets in relation to Barnes’s subject that is inevitably incorporated into both, the system of history and the referential system of fiction. Consequently, through both of the systems, the storytelling and discursively determined subject inevitably obtains its self–acknowledgement within the narrative modes.
Keywords: historiographic metafiction; discourse; subject; Selfhood; temporality; narrative identity